Pengaruh Citra Merek, Kepercayaan dan Promosi Terhadap Keputusan Pembelian Kosmetik Two Way Cake Maybelline di Batam - Larra Vebiola; Muhammad Haldy (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to comprehensively examine the role of brand image, trust, and promotional intensity in shaping purchasing decisions for Maybelline two-way cake cosmetic products in Batam City. The implemented research design adopted a descriptive quantitative approach involving 204 participants who had actual experience in purchasing the product in question. Respondents were determined through purposive sampling technique based on Jacob Cohen's calculations to ensure empirical representativeness of the research sample. Primary data were collected through the distribution of structured questionnaire instruments, then processed and analyzed using hierarchical statistical stages that included testing the validity and reliability of the instrument, verification of classical assumptions, multiple linear regression modeling, and hypothesis testing through partial (t) and simultaneous (F) tests. Empirical findings indicate that brand image contributes 23.9% to purchasing decisions, trust influences 39.1%, while promotion contributes the most dominant influence at 14.7%. The coefficient of determination (R²) value of 82.9% indicates that the three independent variables are simultaneously able to explain variations in consumer purchasing decisions in a substantial proportion. The results of both partial and simultaneous tests confirm a positive and significant influence between brand image, trust, and promotion on purchasing decisions for Maybelline cosmetics in Batam.